Pengaruh Permainan Bowling Terhadap Perkembangan Motorik Kasar Anak Usia Dini Di RA Babul Ilmi Kampung Baru Rantauprapat - Wahyuni Sarah Pohan; Suryatik; Azhar; Muhammad Zulham Munthe (Cendekia Madani Nusantara, 2024)
This research was motivated by the lack of children in rolling the ball in a directed manner, lack of physical fitness training and gross motor learning is not yet varied in children aged 5-6 years. This is because the learning carried out by teachers in the classroom still uses direct learning models with conventional learning models which can make children become bored quickly, so that children do not develop gross motor skills. So researchers use the bowling ball game in the hope that it can help children improve gross motor development in early childhood at RA Babul Ilmi Kampung Baru. This research aims to determine the effect of bowling in early childhood which can influence gross motor development in students at RA Babul Ilmi Kampung Baru Rantauprapat for the 2023-2024 academic year. The population of this study was all RA Babul Ilmi students, totaling 105 students spread across 4 classes. The sample for this research consisted of 30 students, consisting of two classes, namely the Mawar class as an experimental class with a total of 15 students, consisting of 9 girls and 6 boys. The control class is the jasmine class with 15 students, consisting of 9 girls and 6 boys. The method used to collect data is using student observation sheets. Based on hypothesis testing, the value of tcount = 3.319 is obtained, then compared with the value of t at the significant level α = 0.05 with dk = (N1+N2)-2 = 28 found in the table t = 1,701 because the value of tcount > t, namely 3.319 > 1.701, then H is rejected and H is accepted. Thus, it can be concluded that the bottle bowling game media is very effective in improving the gross motor skills of early childhood by RA Babul Ilmi students for the 2023/2024 academic year.